Crisis strategic analysis in enterprise management. - Sobolieva, Tetiana; Kravchenko, Daria (Herald of Economics, 2025)
Introduction. In an environment of economic instability and heightened risks, strategic analysis within the enterprise crisis management system assumes particular significance. Contemporary challenges arising from geopolitical disruptions, shifts in globalization, and evolving economic and technological trends necessitate the development of tools that enhance business resilience and adaptability in high-risk conditions. In this context, crisis strategic analysis serves as a critical mechanism for shaping managerial decisions aimed at preventing crisis phenomena and fostering adaptive responses that support recovery and sustained growth. Consequently, its outcomes not only mitigate the adverse effects of crises but also establish the foundations for enterprise development and enhanced competitiveness.Research purpose. To substantiate the role and develop conceptual foundations of crisis strategic analysis within the enterprise crisis management system, aimed at strengthening resilience, adaptability, and efficiency of managerial decision- making under unstable economic conditions.Research methods. Analysis of scientific publications, systems approach, methods of comparison, critical analysis and conceptual generalization.Results. Crisis strategic analysis as a component of crisis management ensures effective diagnostics of the internal and external environment of the enterprise, identification of risk factors, and formation of adaptive strategies. It is substantiated that the application of crisis strategic analysis contributes to enhancing eficient managerial reactions, enterprise flexibility, timely detection of crisis phenomena, and the development of effective management decisions aimed at long-term development.Prospects. Сrisis strategic analysis plays a key role in maintaining organizational resilience and adaptability by preventing potential threats, ensuring effective response to crises, and restoring stable operations. Further research is required on the issues of improving the tools of crisis strategic analysis in the context of digitalization, scenario forecasting, and a risk-oriented approach.